2021
DOI: 10.1007/s00425-021-03710-4
|View full text |Cite
|
Sign up to set email alerts
|

Beginnings of a plant parasite: early development of Rafflesia consueloae inside its Tetrastigma host

Abstract: Main ConclusionExtensive histology of host organs revealed the early events in the vegetative growth of Rafflesia consueloae including initial infection site, endophyte distribution, and other developmental events prior to bud emergence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Cupule in Rafflesiaceae plants functions as a haustorium, providing nutrients and water [ 90 , 91 ]. Several histoanatomical studies described the process of teardrop-shaped protocorm penetration into the host for flowering in endophytes, and found that the haustorium of Rafflesiaceae plants starts to form in the vascular cambium of the host [ 3 , 61 , 87 , 92 ]; however, the molecular mechanism of haustorium formation is unknown. The process of haustorium formation has been well studied in Orobanchaceae, and is regulated by the LRD program genes [ 43 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cupule in Rafflesiaceae plants functions as a haustorium, providing nutrients and water [ 90 , 91 ]. Several histoanatomical studies described the process of teardrop-shaped protocorm penetration into the host for flowering in endophytes, and found that the haustorium of Rafflesiaceae plants starts to form in the vascular cambium of the host [ 3 , 61 , 87 , 92 ]; however, the molecular mechanism of haustorium formation is unknown. The process of haustorium formation has been well studied in Orobanchaceae, and is regulated by the LRD program genes [ 43 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about how Rafflesiaceae seeds germinate and how endophytic cells enter the host. Apart from multiple locals claiming to have successfully reached flowering in Rafflesia plants grown from seeds [85][86][87], there was no success in vitro [85], suggesting that Rafflesia plants require unknown factor(s) released from the host to flower. Seeds of Orobanchaceae species depend on host-derived SLs to germinate, and most receptors for SLs are encoded by KAI2d, which underwent expansion in S. asiatica and Orobanche cumana genomes [88].…”
Section: Host-parasite Interactionmentioning
confidence: 99%
“…Nonetheless, our study provides a critical first assessment of compounds that differed between infected and non-infected hosts so we may begin to understand how Rafflesia infection affects host metabolomics. It is possible that what we have determined to be "non-infected" hosts may be harboring dormant Rafflesia infection (i.e., Rafflesia buds have not yet emerged, Bascos et al 2021), but given our local guide's expertise and experience in making this determination, and 2014) are provided the low chance of unwittingly selecting three "dormant" samples, we are positive of the sampling, though additional sampling and analysis in the future would certainly be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…(2014a), Sapria endophyte was found in the vascular cambium layer of the host. The newest update, however, revealing the growth activity of Rafflesia endophyte in the xylem as well [BASCOS & al. 2021], which is similar to Rhizanthes [NIKOLOV & al.…”
Section: Host-parasite Intersection Pattern Across Rafflesiaceaementioning
confidence: 99%